Ahmadli, Maya - (:unkn) unknown (My University, 2026)
Maya Ahmadli, PhD in Philology, is a Senior Lecturer at the Department of Foreign Languages, Azerbaijan University of Architecture and Construction (AzUAC). She graduated from the Azerbaijan Pedagogical Institute of Foreign Languages with a degree in English and German Language Teaching and has been teaching English since 1988. She joined AzUAC in 2003 and has served as a Senior Lecturer since 2010. In 2022, she earned her PhD in Philology with a dissertation on passive constructions in English and Azerbaijani. Her research interests include comparative linguistics, syntax, and the linguistic analysis of passive constructions. She is the author of 45 scientific and educational publications, including a monograph, a textbook, a methodological guide, course curricula, and journal articles. Dr. Ahmadli has participated in numerous national and international academic events and faculty exchange programmes in Türkiye. In 2024, she was elected a Corresponding Member of the Baku Branch of the International Academy of Sciences (Innsbruck, Austria) in recognition of her scholarly contributions.